XIII Asean ORLand Head & Neck Congress Siem Reap, Komboja 18-20 November 2009 - Suzina Sheikh, Ab. Hamid (Pusat Pengajian Sains Perubatan, 2009)
Subglottic stenosrs maybe congenital or acquired. Both have typical characteristics and presentations. Despite great advances have been made in the surgrcal techniques, the management of paedratnc subglottic stenosis remains challenging for the otolaryngologist Often the operation is very much tarlored to the needs of the individual patrents. In addition, the surgeon managing the problem must be fully trained in paediatric airway endoscopy and laryngotracheal surgery as inappropriate inrtral management may lead to permanent rntractable sequelae The management rnclude the hrstory of stridor, medrcal history, assessment of seventy of stridor, assessment of the arrway, appropriate treatment and posl-operatrve management The presentation will hrghlrght some of the lessons learned dunng the learnrng curve in the management of paediatnc subglottic stenosis rn Universiti Sains Malaysia